Counts of settled Ostrea edulis larvae on various substrates within three different experimental set-ups - Colsoul, Bérenger; Pouvreau, Stéphane; Di Poi, Carole; Pouil, Simon; Merk, Verena; Peter, Corina; Boersma, Maarten; Pogoda, Bernadette (PANGAEA, 2022)
The dataset compiles counts of larvae of the European flat oyster Ostrea edulis, settled on various substrates under three different experimental conditions. The data was collected within the AWI-RESTORE project (Alfred-Wegener-Institute, Germany), examining basic preconditions for successful restoration of the European flat oyster within the German Bight. The data is separated in three experimental setups: the columns for experiment 1 (hatchery/laboratory) include date stamp in ISO format, Latitude, Longitude, abiotic factors (Flow rate, temperature, salinity, pH, dissolved oxygen), substrate types, area and orientation as well as the count of settled larvae for each set-up. Data for experiment 2 (hatchery) include date stamp in ISO format, Latitude, Longitude, abiotic factors (Flow rate, temperature, salinity, pH), reef number, specifics of examined area and orientation as well as the count of settled larvae for each reef. Columns for experiment 3 (field) include date stamp in ISO format, Latitude, Longitude, abiotic factors (depth, temperature, salinity), chlorophyll concentration, substrate types, specifics and orientation as well as the count of settled larvae for each submerged substrate.
Keywords: bivalves; European flat oyster; Hatchery; marine; Settlement